2022
DOI: 10.1109/tro.2022.3153949
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Impedances to Comply With Constrained Task Dynamics

Abstract: Humans are capable of managing multiple tasks simultaneously. It is widely assumed that human motor control can be emulated by impedance control. To achieve human-like behavior, however, the impedance parameters of multiple tasks may vary during task execution. We propose an algorithm that shapes task impedance as a function of the robot's time-varying inertial properties. These properties involve virtually constrained masses and virtually constrained inertias that counteract a task in order to comply with a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Prior research showed that impedance modulation was necessary to achieve complex manipulation tasks, e.g., managing physical interaction with the environment. 45 , 46 In fact, incorporating time-varying joint-space impedances into the controller could potentially broaden the range of targets that can be successfully hit by the whip, e.g., target 6. Investigating the potential advantages of variable joint-space impedances for complex object manipulation is a topic for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research showed that impedance modulation was necessary to achieve complex manipulation tasks, e.g., managing physical interaction with the environment. 45 , 46 In fact, incorporating time-varying joint-space impedances into the controller could potentially broaden the range of targets that can be successfully hit by the whip, e.g., target 6. Investigating the potential advantages of variable joint-space impedances for complex object manipulation is a topic for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The augmented energy tank described in [19] prevents the energy of the system from suddenly increasing within a single time step, thereby ensuring that the system stays stable. As mentioned in [27], the stored energy in an impedance-controlled robot can be expressed as a storage function S = S c + S r ∈ R, which is composed of the storage functions of the controller and the robot. S r is passive as the robot's energy is physically bounded from below [28].…”
Section: B Energy Tank Integrationmentioning
confidence: 99%
“…Their introduction into industries, such as health care, with complex interactive behaviour has revealed the limitations of traditional industrial controllers. The impedance controller [1][2][3][4][5][6] is a widespread technique enabling robots to interact with uncertain environments. This control technique relies on inverse dynamics modelling to drive the robot to act with a desired mechanical impedance, such as a linear Mass-Spring-Damper system [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Examples are environments that require adaptive trajectories and/or variable impedance gains [8], as well as tasks with uncertain end-effector contact against other agents or the environment (e.g., polishing, physical human-robot collaboration, etc.) [3][4][5][6][9][10][11][12][13]. Such tasks pose various challenges to robots' controllers that currently require an accurate model of contact conditions to ensure system stability.…”
Section: Introductionmentioning
confidence: 99%